Севастопольские рассказы - Толстой Лев Николаевич (Школьная библиотека, 2002)
Экземпляры: ф.21 (2004) / Инвентарный номер: 47647 / Цена: / Сис.шифр: 84(2Рос=Рус)1-4 / Авт.знак: Т 53 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)1-44